Distinct cut task strategy in Australian football players with a history of groin pain. (January 2017) - Edwards, Suzi; Brooke, Hiram C.; Cook, Jill L.
Abstract: Objectives: This study aimed to explore the differences in the magnitude of movement variability and strategies utilized during an unanticipated cut task between players with and without a history of groin pain. Design: Cross-sectional design. Setting: Biomechanics laboratory. Particiants: Male Australian football players with (HISTORY; n = 7) or without (CONTROL; n = 10) a history of groin pain. Outcome measures: Three-dimensional ground reaction forces (GRF) and kinematics were recorded during 10 successful trials of an unanticipated cut task, and isokinetic hip adduction and abduction strength. Between-group differences were determined using independent-samples t -tests and the coefficient of variation (CV). Results: Key substantial between-group differences identified were that the HISTORY group displayed decreased knee flexion and hip internal rotation, increased knee internal rotation and T12-L1 right rotation, and higher GRFs during the cut task. They also utilized three invariant systems (ankle, knee and T12-L1 joints), while being connected by a segment (hip and L5-S1 joints) that displayed increased lumbopelvic movement during the cut task, and decreased adductor muscle strength. Conclusion: This identifies the need for clinical management of the lower limb and thoracic segment to improve functional movement patterns in athletes with a history of a groin injury. Highlights: Players with a history of groin pain display different cut strategies. Movement variability distinguishes players with and without a history of groin pain. Rehabilitation should involve the clinical management of a dynamic movement task.